2000
DOI: 10.1017/s0031182099005478
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary ecology of host-specificity: experimental studies with Strongyloides ratti

Abstract: Factors constraining the evolution of host-specificity were investigated using a gastrointestinal parasitic nematode, Strongyloides ratti. S. ratti is a natural parasite of rats which can also reproduce, with decreased success, in laboratory mice. Observed host-specificity arose from lower establishment, reduced per capita fecundity and more rapid expulsion of parasites from mice relative to rats. Variation in the efficacy of thymus-dependent immunity between host species (rats and mice) was insufficient to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Therefore, the possibility of colonising a new host declines with an increase of the phylogenetic distance among host species. Indeed, studies on host specificity of a related species, Strongyloides ratti, a natural parasite of rats (Rattus rattus), showed that it can complete its life-cycle in laboratory mice (Mus musculus), but with a decreased reproductive success, due to lower establishment rates, earlier expulsion of established parasites and reduced per capita fecundity in mice (Gemmill et al 2000). The authors failed to find the factors underlying the differences in S. ratti fitness among rats and mice, and no evidence for interactions between host and parasite genotypes has been found in later studies (Paterson 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the possibility of colonising a new host declines with an increase of the phylogenetic distance among host species. Indeed, studies on host specificity of a related species, Strongyloides ratti, a natural parasite of rats (Rattus rattus), showed that it can complete its life-cycle in laboratory mice (Mus musculus), but with a decreased reproductive success, due to lower establishment rates, earlier expulsion of established parasites and reduced per capita fecundity in mice (Gemmill et al 2000). The authors failed to find the factors underlying the differences in S. ratti fitness among rats and mice, and no evidence for interactions between host and parasite genotypes has been found in later studies (Paterson 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the dispersion of S. ratti to wild populations of mice seems unlikely, because there have been only two reports of Strongyloides spp. (one of them as S. ratti) in wild-caught mice since the late nineteenth century (Gemmill et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental infection of mice induces patent, but transient, infections that are resolved spontaneously within 2-4 wk and render the mice semiresistant to subsequent infections. Although mice, not being the natural host, display lower worm burden compared with the natural host, the rat, the overall kinetics of infection and immune response are comparable (27)(28)(29). S. ratti infection provokes a classical type 2 response in both species that is characterized by the induction of IL-13, IL-5, IL-3, and IL-10, as well as high titers of S. ratti-specific IgM and IgG1 (30,31).…”
mentioning
confidence: 99%
“…The host range of S. ratti is in comparison to S. mansoni highly limited to a few host species (Brant and Loker, 2013;Gemmill et al, 2000). It is comprehensible that the capability to invade into the non-host skin preparations is reduced, since the surface structure and also the chemical attractants may be different.…”
Section: Figmentioning
confidence: 99%